Lithium ion secondary battery

By adding carboxylate solvent and lithium bisfluorosulfonimide to lithium ion batteries and adjusting the thickness of the separator glue layer, the transmission barrier caused by the blockage of the separator glue layer of the lithium ion battery is solved, and the low-temperature cycling performance is improved. Overcharge safety reduces DC internal resistance.

CN119275354AActive Publication Date: 2025-01-07ZHUHAI COSMX POWER BATTERY CO LTD

Patent Information

Application Number
CN202411362559.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

During the circulation process, the blockage of the diaphragm glue layer of the lithium-ion battery leads to hindering the transmission of lithium ions, and the dynamics of the low-temperature environment and the increase of DC internal resistance, which poses a safety risk.

Method used

Add a highly polar carboxylic acid ester solvent and a high conductivity lithium bisfluorosulfonimide to the electrolyte, and adjust the thickness difference between the first glue layer and the second glue layer in the separator to satisfy the specific relationship. Improve the transmission speed of lithium ions, reduce the DC internal resistance of the battery, improve low-temperature cycling performance and overcharge safety performance.

Benefits of technology

Effectively solve the problem of lithium ion transmission blocked after the diaphragm glue layer is blocked, improve the circulation performance of lithium batteries at low temperatures, reduce the DC internal resistance of the battery, and enhance the battery's overcharge safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275354A_ABST
    Figure CN119275354A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and provides a lithium ion secondary battery, the electrolyte of the lithium ion secondary battery comprises a carboxylic ester solvent and an electrolyte lithium salt, the mass percentage content of the carboxylic ester solvent is A, the mass percentage content of the lithium bis (fluorosulfonyl) imide is B, and the mass percentage content of the lithium bis (fluorosulfonyl) imide is A; the thickness of the first adhesive layer close to one side of the positive plate in the diaphragm is C [mu] m, the thickness of the second adhesive layer close to one side of the negative plate is D [mu] m, and A, B, C and D meet the relational expression that (D-C) / (A + B) is more than or equal to 0.006 and less than or equal to 0.08. The lithium ion secondary battery can effectively solve the problem that lithium ion transmission is blocked after holes are blocked by the diaphragm adhesive layer, the transmission speed of lithium ions in the lithium battery is improved, the direct-current internal resistance of the battery is reduced, the cycle performance of the lithium battery at low temperature is improved, and the overcharge safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion secondary battery. Background Art

[0002] Lithium-ion batteries are widely used in 3C digital, power tools, aerospace, energy storage, power vehicles and other fields due to their advantages such as high specific energy, no memory effect and long cycle life. Lithium-ion batteries include four main materials: positive electrode materials, negative electrode materials, diaphragms and electrolytes. In order to make the battery performance better, the diaphragm is usually coated with ceramics and glue on the base film. The good thermal stability of the ceramic layer can reduce the thermal shrinkage of the diaphragm and improve the safety performance of lithium-ion batteries; the glue layer can enhance the adhesion between the pole piece and the diaphragm to ensure smooth lithium ion migration. In actual production, the contact between the pole piece and the diaphragm is improved through hot pressing process, but the thermal swelling of the diaphragm glue layer will cause the base film to block the pores, hinder the migration of lithium ions, and poor electrolyte infiltration. During the cycle, lithium precipitation will occur, causing safety risks; and when lithium-ion batteries are cycled in a low temperature environment, the base film blockage will cause the dynamics to decrease and the DC internal resistance to increase, resulting in a cycle dive. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and provide a lithium ion secondary battery. By adding a carboxylic acid ester solvent with strong polarity and lithium bis(fluorosulfonyl)imide with high conductivity into the electrolyte and adjusting the thickness difference between the first glue layer and the second glue layer in the diaphragm to satisfy a specific relationship, the problem of obstructed lithium ion transmission after the pores of the diaphragm glue layer are blocked can be effectively solved, the transmission speed of lithium ions in the lithium battery can be increased, the direct current internal resistance (DCR) of the battery can be reduced, and the cycle performance of the lithium battery at low temperature can be improved, and the overcharge safety performance of the battery can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator;

[0005] The electrolyte includes a carboxylate solvent; the mass percentage of the carboxylate solvent is recorded as A based on the total mass of the electrolyte;

[0006] The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as B;

[0007] The diaphragm includes a base film, a first glue layer, a ceramic layer and a second glue layer; the first glue layer is arranged on the surface of the base film close to the positive electrode sheet, and the ceramic layer is arranged between the first glue layer and the base film; the second glue layer is arranged on the surface of the base film close to the negative electrode sheet; the thickness of the first glue layer is recorded as Cμm, and the thickness of the second glue layer is recorded as Dμm;

[0008] Among them, A, B, C and D satisfy the relationship: 0.006≤(DC) / (A+B)≤0.08.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] (1) The lithium-ion secondary battery provided by the present invention can reduce the pore blockage of the diaphragm and effectively solve the problem of lithium ion transmission being blocked after the pore blockage of the diaphragm glue layer, thereby improving the transmission speed of lithium ions in the lithium battery.

[0011] (2) The lithium-ion secondary battery provided by the present invention can reduce the direct current internal resistance (DCR) of the battery.

[0012] (3) The lithium-ion secondary battery provided by the present invention can improve the cycle performance of the lithium battery at low temperatures and improve the overcharge safety of the battery.

[0013] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown is a schematic structural diagram of a diaphragm in an example of the present invention.

[0015] Figure numerals: 1-diaphragm; 11-base film; 12-ceramic layer; 13-first adhesive layer; 14-second adhesive layer; 2-negative electrode sheet; 3-positive electrode sheet. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0018] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0019] In the present invention, the term "average particle size" refers to the average value of diameters of a number (n≥20) of lithium iron phosphate particles, which can be measured by a transmission electron microscope (TEM).

[0020] The present invention provides a lithium ion secondary battery, the battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator;

[0021] The electrolyte includes a carboxylate solvent; the mass percentage of the carboxylate solvent is recorded as A based on the total mass of the electrolyte;

[0022] The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as B;

[0023] The diaphragm includes a base film, a first glue layer, a ceramic layer and a second glue layer; the first glue layer is arranged on the surface of the base film close to the positive electrode sheet, and the ceramic layer is arranged between the first glue layer and the base film; the second glue layer is arranged on the surface of the base film close to the negative electrode sheet; the thickness of the first glue layer is recorded as Cμm, and the thickness of the second glue layer is recorded as Dμm;

[0024] Among them, A, B, C and D satisfy the relationship: 0.006≤(DC) / (A+B)≤0.08.

[0025] In the lithium-ion secondary battery of the present invention, a carboxylate solvent with strong polarity and lithium bis(fluorosulfonyl)imide (LiFSI) with high conductivity are added to the electrolyte, and the diaphragm structure is limited to a first glue layer + a ceramic layer + a base film + a second glue layer (the first glue layer is close to the positive electrode sheet, and the second glue layer is close to the negative electrode sheet). The carboxylate solvent and LiFSI can improve the kinetic properties of the electrolyte, effectively alleviate the poor electrolyte infiltration caused by the diaphragm pore blocking, and improve the transmission performance of lithium ions. The higher the value of A+B, the better the kinetics and wettability of the electrolyte, but the side reactions of the electrolyte will increase at high temperatures, resulting in poor high-temperature performance of the battery and prone to thermal runaway; at the same time, the DC difference is adjusted to increase, D increases, and C remains unchanged, so that the ratio of (DC) / (A+B) is maintained in the range of 0.006-0.08, and the positive and negative active particles are less wrapped by the first glue layer and the second glue layer, which is beneficial to increase the lithium ion migration channel; and when A+B increases, the solvation structure formed by lithium ions coordinated by the solvent has an increased solvation radius, a low HOMO energy level, and better heat and pressure resistance; adjusting the DC difference to increase can increase the lithium ion migration channel, so that the transmission of the lithium ion solvation structure is not affected, and the increase in the solvation structure can improve the stability of the electrolyte at high temperatures, reduce decomposition and gas production, and alleviate the problem of poor high-temperature performance caused by the increase in the A+B value.

[0026] In general, in order to improve the kinetics of the electrolyte, reduce the adverse effects caused by excessive and low contents of carboxylate solvents and LiFSI, and reduce the problem of poor lithium ion transmission caused by diaphragm plugging. The present invention has found that when A, B, C and D satisfy the relationship 0.006≤(DC) / (A+B)≤0.08, the kinetics of the electrolyte can be effectively improved, the wettability of the electrolyte can be improved, the diaphragm plugging can be reduced, and the problem of lithium ion transmission being blocked after the diaphragm glue layer plugging can be effectively solved, the transmission speed of lithium ions in the lithium battery can be improved, the DC internal resistance (DCR) of the battery can be reduced, and the cycle performance of the lithium battery at low temperatures can be improved, and the overcharge safety performance of the battery can be improved.

[0027] In some embodiments, the structure of the membrane is as follows Figure 1 As shown, the diaphragm 1 includes a base film 11, a ceramic layer 12 is provided on the surface of the base film 11 close to the positive electrode sheet 3, a first glue layer 13 is provided on the surface of the ceramic layer 12 close to the positive electrode sheet 3, that is, the ceramic layer 12 is provided between the first glue layer 13 and the base film 11; a second glue layer 14 is provided on the surface of the base film 11 close to the negative electrode sheet 2.

[0028] In some embodiments, the ratio of (DC) / (A+B) can be, for example, 0.006, 0.0062, 0.0065, 0.0068, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.065, 0.07, 0.0769, 0.078, 0.08, preferably 0.02≤(DC) / (A+B)≤0.065. When calculating the ratio (DC) / (A+B), the units of D and C are μm, and only the numbers are considered when calculating D and C; A and B are percentages, and only the numbers before the percentage sign are considered when calculating. For example, D=3.0 μm, C=2.0 μm, A=40%, B=10%, then (DC) / (A+B)=(3-2) / (40+10)=0.02.

[0029] In some embodiments, D and C satisfy the relationship: 0.1≤DC≤1.5, and the difference of DC is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5. Preferably, the thickness C of the first adhesive layer is 0.5 μm to 2.5 μm, for example, C is 0.5 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.5 μm. Preferably, the thickness D of the second adhesive layer is 0.6 μm to 4.0 μm, for example, D is 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, or 4.0 μm.

[0030] Under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, the difference of DC is further adjusted, and when the values ​​of D and C are within the above range, the thickness of the second glue layer can be controlled to be greater than the thickness of the first glue layer, and the thickness difference is within an appropriate range, thereby reducing the pore blocking phenomenon of the diaphragm glue layer, reducing the DCR of the battery, and improving the transmission performance of lithium ions, thereby improving the fast charging cycle performance of the battery; avoid the DC difference being too small, that is, when D is large and C is also large, the thickness of the first glue layer and the second glue layer is large, resulting in a longer lithium ion migration channel and reduced kinetics, leading to a lithium precipitation dive in the low-temperature cycle of the battery; it can also avoid the DC difference being too large, that is, when D is large and C is small, resulting in weak adhesion between the positive electrode sheet and the diaphragm, resulting in obstruction of the ion channel, and failure to effectively improve the transmission of lithium ions.

[0031] In some embodiments, A and B satisfy the relationship: 13≤A+B≤81; for example, the value of A+B can be 13, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 80.5, 81. Preferably, the mass percentage content A of the carboxylate solvent is 10% to 70%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, preferably 20% to 50%. Preferably, the mass percentage content B of the lithium bis(fluorosulfonyl)imide is 1.5% to 14%, for example, it can be 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 10.5%, 11%, 12%, 13%, 13.5%, 14%, more preferably 3.0%-11%.

[0032] Under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, further adjusting the value of A+B and keeping the values ​​of A and B within the above range can better improve the dynamics and wettability of the electrolyte, improve the transmission performance of lithium ions when the diaphragm is blocked, thereby improving the fast charging cycle performance of the battery and reducing lithium plating of the battery; avoid the situation where the value of A+B is too high (both the values ​​of A and B are too high), resulting in poor high temperature performance of the battery, reducing the risk of battery combustion, and thus improving the safety performance of the battery; and avoid the situation where the value of A+B is too low (both the values ​​of A and B are too low), resulting in insufficient dynamics of the electrolyte and the inability to improve the transmission of lithium ions.

[0033] In some embodiments, the carboxylate solvent includes at least one of MA (methyl acetate), EA (ethyl acetate), EP (ethyl propionate), and EB (ethyl butyrate).

[0034] In some embodiments, the electrolyte further includes a carbonate solvent, and the carbonate solvent includes at least two of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate. Under the condition that A, B, C, and D satisfy 0.006≤(DC) / (A+B)≤0.08, the electrolyte is adjusted to further add a carbonate solvent, which can make the interface of the electrolyte generated at the negative electrode more stable, improve the cycle performance of the battery, and improve the safety performance of the battery.

[0035] In some embodiments, the base film comprises a polyolefin material, for example, at least one of polyethylene PE, polypropylene PP, polyethylene terephthalate, polyimide, PE and PP composite structures. Preferably, the base film has a thickness of 3 μm-20 μm and a porosity of 20%-60%.

[0036] In some embodiments, the ceramic layer material includes one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and nickel oxide. Preferably, the thickness of the ceramic layer is 1 μm to 5 μm. Preferably, the Dv50 of the ceramic layer material is 0.5 μm to 5.0 μm.

[0037] In some embodiments, the first adhesive layer and the second adhesive layer are conventional spray-coated adhesive layers, for example, the first adhesive layer and the second adhesive layer independently include one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene modified and its copolymer, polyimide, butyl acrylate-acrylonitrile copolymer, polyacrylonitrile, aramid resin, polymethyl methacrylate, polyacrylic acid, ethylene-acrylic acid copolymer, polymethyl acrylate, polyethyl acrylate, styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose, polyvinyl alcohol and copolymer-modified polyvinyl alcohol thereof.

[0038] In some embodiments, the peeling force between the positive electrode sheet and the separator is recorded as XN / m, and the peeling force between the negative electrode sheet and the separator is recorded as YN / m; wherein B, X and Y satisfy the relationship: 1.5≤B / (X / Y)≤14, and the ratio of B / (X / Y) can be, for example, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. When B / (X / Y) calculates the ratio, B is a percentage, and only the numbers before the percentage sign are considered in the calculation; the units of X and Y are N / m, and only the numbers are considered in the calculation of X and Y. For example, when B=5%, X=5N / m, and Y=4N / m, B / (X / Y)=5 / (5 / 4)=4. The test method for the peeling force between the electrode sheet and the separator includes performing a T-type peeling test using a universal tensile machine.

[0039] The ratio of X / Y represents the ratio of the peeling force between the positive and negative electrodes and the separator. Since a ceramic layer is also provided on the positive electrode side of the present invention, the peeling force between the positive electrode sheet and the separator is greater, and the ratio of X / Y is usually greater than 1. However, the larger the ratio of X / Y, the greater the difference in the bonding force between the positive and negative electrode sheets and the separator. If X is larger, the thickness of the first adhesive layer will be smaller, causing the positive electrode particles to be surrounded by the separator adhesive layer, blocking the lithium ion migration channel, reducing the kinetics, and causing the lithium precipitation rate to drop in low-temperature cycles. Therefore, under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, further adjusting the relationship between the LiFSI content and the stripping force in the electrolyte to satisfy B, X and Y to satisfy 1.5≤B / (X / Y)≤14 can improve the dynamics of the electrolyte and enhance the low-temperature cycle performance of the battery; avoid the B / (X / Y) ratio being too small, the B content being too low or the X / Y ratio being too large, which affects the dynamics of the electrolyte; and avoid the B / (X / Y) ratio being too large, the B content being too high, resulting in poor high-temperature performance of the battery.

[0040] In some embodiments, X satisfies 0.2N / m≤X≤10N / m, for example, X can be 0.2N / m, 0.5N / m, 0.8N / m, 1N / m, 2N / m, 3N / m, 4N / m, 5N / m, 6N / m, 7N / m, 8N / m, 9N / m, 10N / m. In some embodiments, Y satisfies 0.1N / m≤Y≤10N / m, for example, Y can be 0.1N / m, 0.2N / m, 0.5N / m, 1N / m, 2N / m, 3N / m, 4N / m, 5N / m, 6N / m, 7N / m, 8N / m, 9N / m, 10N / m. When the relationship between the LiFSI content and the stripping force in the electrolyte satisfies B, X and Y satisfy 1.5≤B / (X / Y)≤14, and the values ​​of X and Y are further adjusted within the above range, the adhesion between the positive and negative electrode sheets and the separator can be improved, the electrochemical system can be more integrated, the resistance during lithium ion migration can be reduced, the lithium ion transmission performance can be improved, and the fast charging performance of the battery can be improved.

[0041] In some embodiments, the porosity of the negative electrode sheet is recorded as E; wherein B, D and E satisfy the relationship: 0.3≤B / (D+E)≤12; the value of B / (D+E) can be, for example, 0.3, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, preferably 0.85≤B / (D+E)≤8.5. Preferably, the porosity E of the negative electrode sheet is 20% to 40%, for example, E can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%. When calculating the ratio of B / (D+E), B is a percentage, and only the digits before the percentage sign are considered in the calculation; the unit of D is μm, and only the digits are considered in the calculation of D; E is a percentage, but it is written in the form of a decimal when calculated. For example, when B=5%, D=1 μm, and E=20%, B / (D+E)=5 / (1+0.2)=4.17.

[0042] The test method for the porosity of the negative electrode sheet refers to the measurement method and measurement conditions of the true density of powder in the national standard GB / T 5162-2006 "Measurement method of true density of powder".

[0043] The thinner the second adhesive layer of the diaphragm is after hot pressing, the tighter it adheres to the negative electrode, which causes pore blockage (i.e., the porosity of the diaphragm is reduced, i.e., D is reduced, and E is also reduced), and the electrolyte infiltration path is blocked, resulting in poor dynamics and battery low-temperature cycle plunge. Therefore, under the condition that A, B, C and D meet 0.006≤(DC) / (A+B)≤0.08, B, D and E are further adjusted to meet the condition of 0.3≤B / (D+E)≤12. When B / (D+E) is larger, the content B of LiFSI is higher, which is beneficial to improving the dynamics of the electrolyte; at the same time, increasing D+E can reduce the pore blockage problem of the diaphragm on the negative electrode side; but when B / (D+E) is too large, for example, when B / (D+E) exceeds 12, the content B of LiFSI is too high, which is easy to cause poor overcharge safety performance of the battery. When B / (D+E) is too small, that is, the content of LiFSI is low, and D+E is reduced at the same time, it is easy to cause insufficient kinetics of the electrolyte, and the negative electrode side diaphragm is easy to be blocked, which cannot improve the problems of low-temperature cycle jump, DCR increase and overcharge safety risk caused by diaphragm blockage. Therefore, when B, D and E meet the conditions of 0.3≤B / (D+E)≤12, the kinetics of the electrolyte can be better improved, the wettability of the electrolyte can be improved, and the problems such as reduced internal resistance and cycle jump caused by diaphragm blockage can be reduced.

[0044] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the Dv50 of the negative electrode active material is denoted as F; the first adhesive layer includes a first polymer, and the average particle size of the first polymer is denoted as G; G and F satisfy: 50*G < F. Preferably, the Dv50 of the negative electrode active material is 5 μm to 20 μm. For example, the Dv50 can be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm; preferably, the average particle size G of the first polymer is 0.1 μm to 0.5 μm. For example, G can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm. When calculating 50*G < F, the unit of G is μm and the unit of F is μm, and the unit can be not considered in the calculation. For example, G = 0.2 μm, F = 15 μm, 50*0.2 < 15.

[0045] In the first adhesive layer of the separator, when 50 times the average particle size of the first polymer is greater than the D50 of the negative electrode material (i.e., 50*G > F, when the condition of 50*G < F of the present invention is not satisfied), after hot pressing, the first polymer undergoes thermal swelling and wraps the negative electrode active material particles, resulting in the blockage of the lithium insertion channels. Lithium ions are reduced to lithium metal by obtaining electrons on the surface of the negative electrode. As the battery is charged, lithium dendrites are further formed and pierce the separator, leading to battery fire and causing safety accidents. Therefore, when the present invention adjusts 50*G < F, it can further reduce lithium plating in the battery, improve the cycle performance of the battery, and improve the safety performance of the battery.

[0046] In some embodiments, the coverage rate of the first adhesive layer is 5% to 96%, for example, it can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 96%, and more preferably 20 - 40%.

[0047] In some embodiments, the coverage rate of the second adhesive layer on the base film is 5% to 96%, for example, it can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 96%, and more preferably 20 - 40%.

[0048] The test method for the coverage rate of the first adhesive layer and the coverage rate of the second adhesive layer includes taking a separator of a unit area and testing the covered area of the adhesive layer on the base film with a scanning electron microscope, which is denoted as the coverage rate.

[0049] When A, B, C, and D satisfy the condition of 0.006 ≤ (D - C) / (A + B) ≤ 0.08, when further adjusting the coverage rate of the first adhesive layer and the coverage rate of the second adhesive layer within the above range, the problem of pore blockage of the separator adhesive layer can be reduced, the DCR of the battery can be effectively reduced, and the problems of hindered lithium ion migration caused by pore blockage of the adhesive layer, resulting in low-temperature cycle diving and high overcharge safety risks, can be reduced.

[0050] In some embodiments, the electrolyte includes a sulfate additive; based on the total mass of the electrolyte, the mass percentage of the sulfate additive is 0.1% to 2%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%. Under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, the sulfate additive is added to the electrolyte, and the sulfate additive reacts with the electrolyte to generate lithium sulfite, which can increase ion conductivity, reduce battery impedance, make the transmission of lithium ions inside the battery smoother, and improve the high-temperature fast charging performance of the battery.

[0051] In some embodiments, the sulfate ester additive includes one or more of the following compounds:

[0052]

[0053]

[0054] In some embodiments, the electrolyte includes a carbonate additive; based on the total mass of the electrolyte, the mass percentage of the carbonate additive is 0.1% to 2%, for example, 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%. Under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, the carbonate additive is added to the electrolyte, and the carbonate additive is reduced to form a SEI film at the negative electrode before the ethyl acetate solvent, thereby inhibiting the side reaction on the electrode surface, reducing the generation of side reaction products, and improving the high temperature performance of the battery.

[0055] In some embodiments, the carbonate additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), trifluoromethylethylene carbonate (TFEC), 1,2-difluoroethylene carbonate (DFEC), and bis(ethylene carbonate) (EC).

[0056] In some embodiments, the electrolyte further comprises a lithium salt additive; based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.1% to 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. Preferably, the lithium salt additive comprises lithium difluorophosphate (LiPO 2 F 2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate (LiODFP), lithium tetrafluoroborate (LiBF4), lithium tetrafluorooxalatophosphate (LiTFOP). Under the condition that A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, the above-mentioned lithium salt additive is added to the electrolyte. The lithium salt additive can improve the ionic conductivity of the electrolyte, make the migration rate of lithium ions in the electrolyte faster, and thus improve the fast charging performance of the battery.

[0057] In some embodiments, the electrolyte lithium salt further includes lithium hexafluorophosphate.

[0058] In some embodiments, in the lithium-ion secondary battery, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector; the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes lithium iron phosphate. Preferably, the Dv50 of the lithium iron phosphate is 0.5μm-1.5μm; the specific surface area BET is 5m 2 / g-15m 2 / g.

[0059] In some embodiments, in the lithium-ion secondary battery, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector; the negative electrode active material layer includes a negative electrode active material; the negative electrode active material includes at least one of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials and lithium-containing metal composite oxide materials.

[0060] In some embodiments, the lithium-ion secondary battery may be a power lithium battery, a consumer lithium battery, or an energy storage lithium battery.

[0061] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0063] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0064] The batteries of the examples and comparative examples of the present invention were prepared according to the following preparation method, and the differences from Example 1-1 are shown below.

[0065] Example 1-1

[0066] (1) Preparation of positive electrode sheet:

[0067] LiFePO 4 ), conductive carbon (Super-P) and polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone in a mass ratio of about 97:1:2, and stirred evenly to obtain a positive electrode slurry. The slurry is coated on an aluminum foil with a thickness of about 12 μm, dried, cold pressed, and then cut and welded to obtain a positive electrode sheet.

[0068] (2) Preparation of negative electrode sheet:

[0069] Graphite, conductive carbon (Super-P), styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC) were mixed in a solvent deionized water at a mass ratio of about 96.5:1.5:1:1, and stirred evenly to obtain a negative electrode slurry. The slurry was coated on a copper foil with a thickness of about 8 μm, dried, cold pressed, and then cut and welded to obtain a negative electrode sheet.

[0070] (3) Preparation of electrolyte

[0071] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and carboxylate solvent EA are mixed evenly (wherein the percentage of EA in the electrolyte is A, the percentage of EC in the electrolyte is 30%, and the content of EMC in the electrolyte is obtained according to calculation), and fully dried lithium hexafluorophosphate, 2.5wt% vinylene carbonate and other additives (specific amounts and selections are shown in Table 1) based on the total mass percentage of the electrolyte are quickly added to the mixed solution, and the electrolyte is obtained by stirring.

[0072] (4) Preparation of lithium-ion batteries

[0073] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked by a Z-type stacking machine to obtain a bare cell without liquid injection; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell, and the desired lithium-ion battery is obtained through vacuum packaging, standing, formation, secondary sealing, sorting and other processes. In the separator, the thickness C of the first glue layer and the thickness D of the second glue layer are shown in Table 1.

[0074] (5) Test battery

[0075] (i) -10℃ cycle test

[0076] The batteries obtained in the above examples and comparative examples were placed in a (-10±2)℃ environment and left to stand for 2-3 hours. When the battery body reached (-10±2)℃, the battery was charged at 0.5C to 3.65V and then cut off at 0.05C, left to stand for 5 minutes, and discharged at 0.5C to 2.5V, left to stand for 5 minutes. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q. When the cycle reached the required number of times, the last discharge capacity of the battery was recorded as Q1. The calculation formula used is as follows: Capacity retention rate (%) = Q1 / Q×100%.

[0077] (ii) -10℃ 50% SOC DCR test

[0078] Place the battery in a -10±2℃ environment, leave it for 120min, discharge it to 2.5V at 0.5C constant current, leave it for 30min, charge it to 3.65V at 0.5C constant current and constant voltage, cut off current 0.05C, leave it for 30min, discharge it to 2.5V at 0.5C constant current, record the discharge capacity C0, leave it for 30min, charge it to 3.65V at 1C constant current and constant voltage, cut off current 0.05C, leave it for 30min, discharge it to 50% SOC at 1C, i.e. C0*(1-50% SOC), leave it for 120min in a -10℃±1℃ environment, discharge it at 3C for 10S (sampling time 100ms), record the end voltage of the shelf as V1, the end voltage of the discharge as V2, and the actual discharge current as I, then the calculation formula of 25℃ 50% SOCDCR is: DCR=(V1-V2) / I;

[0079] (iii) 45℃ cycle test

[0080] Place the battery in a 45±2℃ environment, leave it for 180min, discharge it to 2.5V at 1C constant current, leave it for 30min, charge it to 3.65V at 1C constant current and constant voltage, cut off current 0.05C, leave it for 30min, discharge it to 2.5V at 1C constant current, record the discharge capacity C0, leave it for 30min, charge it to 3.65V at 1.0C0 constant current and constant voltage, cut off current 0.05C0, leave it for 30min, discharge it to 2.5V at 1.0C0 constant current, when the cycle reaches n times, record the last discharge capacity Cn, the capacity retention rate of the nth cycle is calculated as follows: Capacity retention rate (%) = Cn / C0×100%

[0081] (iv) 25℃ 5.5V overcharge test

[0082] Place the battery in a 25±2℃ environment for 180 minutes, overcharge it to 5.5V at a constant current of 1C, and observe whether the battery catches fire during this process.

[0083] Referring to Example 1-1, the content of EA was changed in Examples 1-1 to 1-4 and Comparative Example 1 in Example 1, and the type of carboxylic acid ester was changed in Examples 1-5 to 1-7 (MA in Example 1-5, EP in Example 1-6, and EB in Example 1-7); the content of LiFSI was changed in Example 2; the thickness of the first adhesive layer and the thickness of the second adhesive layer were changed in Example 3; EA and LiFSI were not added in Comparative Example 2. The specific differences are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] Note: “ / ” indicates that the corresponding parameter is not tested.

[0088] It can be seen from Table 1 that when A, B, C and D satisfy 0.006≤(DC) / (A+B)≤0.08, the cycle performance of the lithium battery at low and high temperatures can be effectively improved, the DC internal resistance (DCR) of the battery can be reduced, and the overcharge safety performance of the battery can be improved.

[0089] Referring to Example 1-1, in Example 4, the peeling force of the positive electrode sheet and the negative electrode sheet was adjusted by changing the thickness of the glue layer. The specific differences are shown in Table 2.

[0090] Table 2

[0091]

[0092]

[0093] It can be seen from Table 2 that when the relationship between the LiFSI content and the stripping force in the electrolyte is adjusted to satisfy B, X and Y satisfying 1.5≤B / (X / Y)≤14, the dynamics of the electrolyte can be improved and the low-temperature cycle performance and high-temperature cycle performance of the battery can be improved.

[0094] Referring to Example 1-1, the thickness of the second glue layer and the porosity of the negative electrode sheet were changed in Example 5. The specific differences are shown in Table 3.

[0095] Table 3

[0096]

[0097] It can be seen from Table 3 that when B, D and E meet the condition of 0.3≤B / (D+E)≤12, they can better improve the dynamics of the electrolyte, improve the wettability of the electrolyte, reduce the problems of internal resistance reduction and cycle diving caused by diaphragm blockage, and improve the low-temperature cycle performance and high-temperature cycle performance of the battery.

[0098] Referring to Example 1-1, in the sixth group of examples, the coverage rates of the first adhesive layer and the second adhesive layer were adjusted by changing the thickness during the coating of the adhesive layer, and in the seventh group of examples, the Dv50 of the negative active material and the average particle size of the first polymer were changed. The specific differences are shown in Table 4.

[0099] Table 4

[0100]

[0101]

[0102] As can be seen from Table 4, when the coverage rates of the first adhesive layer and the second adhesive layer in the sixth group of examples are within the preferred range, the DCR of the battery can be reduced, and the problem of the hindered migration of lithium ions caused by the blockage of the adhesive layer pores resulting in the low-temperature cycle dive can be reduced. In the seventh group of examples, when 50*G<F is adjusted, the lithium plating of the battery can be further reduced, the cycle performance of the battery can be improved, and the safety performance of the battery can be improved.

[0103] Carried out with reference to Example 1-1, in the eighth group of examples, the types of additives in the electrolyte were changed. The specific differences are shown in Table 5.

[0104] Table 5

[0105]

[0106] Note: " / " indicates that the corresponding additive was not added.

[0107] As can be seen from Table 5, adding sulfate additives, carbonate additives, and lithium salt additives to the electrolyte can improve the low-temperature and high-temperature cycle performance of the battery and reduce the internal resistance.

[0108] It should be noted that in this article, the term "including", "comprising", or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article, or device including a series of elements not only includes those elements but also includes other elements not expressly listed, or further includes elements inherent to such process, method, article, or device. Without further limitation, an element defined by the phrase "including a..." does not exclude the existence of additional identical elements in the process, method, article, or device including that element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in a reverse order according to the functions involved. For example, the described method may be performed in an order different from that described, and various steps may be added, omitted, or combined. Additionally, the features described with reference to certain examples may be combined in other examples.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator; The electrolyte includes a carboxylate solvent; the mass percentage of the carboxylate solvent is recorded as A based on the total mass of the electrolyte; The electrolyte includes an electrolyte lithium salt, and the electrolyte lithium salt includes lithium bis(fluorosulfonyl)imide; based on the total mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is recorded as B; The diaphragm comprises a base film, a first glue layer, a ceramic layer and a second glue layer; the first glue layer is arranged on the surface of the base film close to the positive electrode sheet, and the ceramic layer is arranged between the first glue layer and the base film; the second glue layer is arranged on the surface of the base film close to the negative electrode sheet; The thickness of the first adhesive layer is recorded as C μm, and the thickness of the second adhesive layer is recorded as D μm; Among them, A, B, C and D satisfy the relationship: 0.006≤(DC) / (A+B)≤0.

08.

2. The lithium ion secondary battery according to claim 1, characterized in that: A, B, C and D satisfy the relationship: 0.02≤(DC) / (A+B)≤0.065; Preferably, D and C satisfy the relationship: 0.1≤DC≤1.5; Preferably, A and B satisfy the relationship: 13≤A+B≤81.

3. The lithium ion secondary battery according to claim 2, characterized in that: The mass percentage A of the carboxylate solvent is 10% to 70%; Preferably, the mass percentage B of the lithium bis(fluorosulfonyl)imide is 1.5% to 14%; Preferably, the thickness C of the first adhesive layer is 0.5 μm to 2.5 μm; Preferably, the thickness D of the second adhesive layer is 0.6 μm to 4.0 μm.

4. The lithium-ion secondary battery according to claim 1, characterized in that: The peeling force between the positive electrode sheet and the separator is recorded as XN / m, and the peeling force between the negative electrode sheet and the separator is recorded as YN / m; wherein B, X and Y satisfy the relationship: 1.5≤B / (X / Y)≤14; Preferably, X satisfies 0.2N / m≤X≤10N / m; Preferably, Y satisfies 0.1 N / m≤Y≤10 N / m.

5. The lithium ion secondary battery according to claim 1, characterized in that: The porosity of the negative electrode sheet is recorded as E; wherein B, D and E satisfy the relationship: 0.3≤B / (D+E)≤12; Preferably, the porosity E of the negative electrode sheet is 20% to 40%.

6. The lithium ion secondary battery according to claim 1, characterized in that: The negative electrode sheet includes a negative electrode active material, and the Dv50 of the negative electrode active material is recorded as F; the first glue layer includes a first polymer, and the average particle size of the first polymer is recorded as G; G and F satisfy: 50*G <F; Preferably, the Dv50 F of the negative electrode active material is 5 μm to 20 μm; Preferably, the average particle size G of the first polymer is 0.1 μm to 0.5 μm.

7. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The coverage of the first adhesive layer and the second adhesive layer on the base film is independently 5% to 96%, more preferably 20% to 40%; Preferably, the carboxylate solvent comprises at least one of methyl acetate, ethyl acetate, ethyl propionate, and ethyl butyrate; Preferably, the electrolyte further includes a carbonate solvent, and the carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate.

8. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The electrolyte includes a sulfate ester additive; the mass percentage of the sulfate ester additive is 0.1% to 2% based on the total mass of the electrolyte; Preferably, the sulfate additive comprises one or more of the following compounds:

9. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The electrolyte includes a carbonate additive; the mass percentage of the carbonate additive is 0.1% to 2% based on the total mass of the electrolyte; Preferably, the carbonate additive includes at least one of fluoroethylene carbonate, vinylene carbonate, vinylethylene carbonate, trifluoromethylethylene carbonate, 1,2-difluoroethylene carbonate and bisethylene carbonate.

10. The lithium ion secondary battery according to any one of claims 1 to 6, characterized in that: The electrolyte further comprises a lithium salt additive; the mass percentage of the lithium salt additive is 0.1% to 1% based on the total mass of the electrolyte; Preferably, the lithium salt additive includes at least one of lithium difluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm and lithium ion battery containing same

    CN110556495A

  • Lithium ion battery

    CN113410510A

  • Battery

    CN114142176A

  • Lithium-ion battery

    WO2022257859A1

Cited By

  • Lithium ion battery

    CN120749230A

  • Lithium ion battery

    CN121307153A